2018
DOI: 10.4209/aaqr.2017.02.0070
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Characteristics of Black Carbon Aerosol and its Potential Source Regions in Baoji, China

Abstract: Continuous measurements of black carbon (BC) aerosol were made at a midsized urban site in Baoji, China, in 2015. The daily average mass concentrations varied from 0.6 to 11.5 µg m -3 , with an annual mean value of 2.9 ± 1.7 µg m -3 . The monthly variation indicated that the largest loading of BC occurred in January and the smallest in June. The mass concentrations exhibited strong seasonality, with the highest occurring in winter and the lowest in summer. The large BC loadings in winter were attributed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Compared with other rural areas, the average BC concentrations in rural Qingdao were much lower than those in Beijing of China [34] and Delhi of India [27] and slightly higher than those in Mahabaleshwar of India [18] and Byeongcheon of Korea [56]. BC concentrations in both urban areas [18,19,26,36,[57][58][59][60][61][62] and suburban areas [47,55] were higher than those in rural Qingdao areas. The BC concentrations in the remote background areas [24,63,64] were much lower than those in the rural areas of Qingdao.…”
Section: Overview Of Bc Concentrationsmentioning
confidence: 75%
See 3 more Smart Citations
“…Compared with other rural areas, the average BC concentrations in rural Qingdao were much lower than those in Beijing of China [34] and Delhi of India [27] and slightly higher than those in Mahabaleshwar of India [18] and Byeongcheon of Korea [56]. BC concentrations in both urban areas [18,19,26,36,[57][58][59][60][61][62] and suburban areas [47,55] were higher than those in rural Qingdao areas. The BC concentrations in the remote background areas [24,63,64] were much lower than those in the rural areas of Qingdao.…”
Section: Overview Of Bc Concentrationsmentioning
confidence: 75%
“…CO, a gaseous pollutant from incomplete combustion, showed the same monthly variation as BC, and PM2.5 and BC show the same peak and trough in the monthly pattern, which indicated that BC and combustion-generated atmospheric pollutants have common sources from Qingdao and its surrounding areas. These results indicate that the increase in local and regional anthropogenic primary emissions and adverse meteorological conditions lead to serious pollution of BC in winter [19,36,62], combined with the seasonal distribution pattern meteorological parameters and gas pollution. In each symbol, the whiskers above and below box mark the 90% and 10% percentiles, respectively; the upper and lower edge of the boxes represent the 75% and 25% percentiles, respectively; and the lines and circles inside the boxes denote median and mean values, respectively.…”
Section: Seasonal Variationsmentioning
confidence: 83%
See 2 more Smart Citations
“…The sampling film used in the aethalometer has strong scattering effects, which disturb the absorption calculation, thereby introducing some errors. Therefore, the measurements of the raw aethalometer need to be corrected [19].…”
Section: Data Collection and Processingmentioning
confidence: 99%